Một phương án thiết kế cài đặt bộ chữ Việt trên máy vi tính - Chi, Dao Huu; Manh, Le (Journal of Computer Science and Cybernetics, 2018)
In this article we will discuss two main project for the Vietnamese language on 16 bit micro computers: -         Storing in RAM in a manner which is as similar as the display on the screen (using codes in the second half of the ASCII  table). -          Storing in RAM in a manner which is different than the display on the screen (using 10 free codes in the ASCII  table). The first project has been implemented successfully. However, it has also few essential defects in which the most important is the unwarranty of the Vietnamese lexical sorting order. That is why the second project should be preferable. Several suggestions to  the implementation of  the second project are given. Also given in the annex A the VNCII (Vietnamese code for information interchange) table.